2015
DOI: 10.1111/1365-2656.12369
|View full text |Cite
|
Sign up to set email alerts
|

Informed herbivore movement and interplant communication determine the effects of induced resistance in an individual‐based model

Abstract: Summary1. Plant induced resistance to herbivory affects the spatial distribution of herbivores, as well as their performance. In recent years, theories regarding the benefit to plants of induced resistance have shifted from ideas of optimal resource allocation towards a more eclectic set of theories that consider spatial and temporal plant variability and the spatial distribution of herbivores among plants. However, consensus is lacking on whether induced resistance causes increased herbivore aggregation or in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 55 publications
0
42
0
Order By: Relevance
“…Previous modelling suggested that induced resistance in S. altissima could influence spatial distributions of the goldenrod specialist T. virgata (Rubin et al . ). The model predicted how movement from induced to uninduced plants altered herbivore distributions, and the ability of plants to anticipate attack resulted in more even distributions, suggesting that a gradation of primed defences over distances of a meter are likely to have profound effects on the distribution of herbivores, with possible ramifications for the entire goldenrod community (Rubin et al .…”
Section: Discussionmentioning
confidence: 97%
“…Previous modelling suggested that induced resistance in S. altissima could influence spatial distributions of the goldenrod specialist T. virgata (Rubin et al . ). The model predicted how movement from induced to uninduced plants altered herbivore distributions, and the ability of plants to anticipate attack resulted in more even distributions, suggesting that a gradation of primed defences over distances of a meter are likely to have profound effects on the distribution of herbivores, with possible ramifications for the entire goldenrod community (Rubin et al .…”
Section: Discussionmentioning
confidence: 97%
“…This was predicted for an herbivore like T. virgata because mobile, selectively feeding herbivores (Rubin et al . ) move more frequently within and between herbivore‐induced plants (Fernandes et al . ) and benefit by maximizing their time spent feeding on uninduced tissues (Paschold, Halitschke & Baldwin ; Karban ).…”
Section: Discussionmentioning
confidence: 99%
“…This conclusion is supported by a recent model (Rubin et al . ) that found that the transfer of chemical information between neighbouring plants is more important for a more even distribution of beetle herbivory within the plant population (risk spreading) than the transfer of information to the herbivore, with a combined effect (induced resistance plus plant communication) being the strongest. This, in combination with our data, may explain the earlier observations that herbivore loads on individual plants are relatively low more than 75% of the time (except during outbreaks) and that at these low loads, herbivory has no measurable effect on S. altissima 's fitness (Root ).…”
Section: Discussionmentioning
confidence: 99%
“…By implementing informed emigration and random immigration, species in our model performed informed, but not optimal habitat selection. In theory, less‐than‐optimal dispersal can decrease the effectiveness of predators in suppressing prey at the landscape scale (Holt, 1985); while informed dispersal would result in higher aggregation of predators (Rubin, Ellner, Kessler, & Morrell, 2015). …”
Section: Methodsmentioning
confidence: 99%